The Innovative Path of AI Technology Empowering Marketing Strategy in Unmanned Supermarkets - Tang, Na; Li, Yiding; Liang, Yuting; He, Qiqi; Jiang, Wenxin (LPPM STIKI Malang, 2024)
This research , whose research objects are users’ experiences, is a quantitative research t through methods such as literature method, questionnaire survey, and data analysis. The results show that the impact of unmanned supermarket technology on shopping experience, the evaluation of unmanned supermarket service and safety, and the correlation between technical difficulties and shopping frequency are the most important factors affecting user experience. Among them, the diversity of checkout technology and service response speed contribute the most. These analysis results provide important theoretical support and reference for unmanned supermarkets to optimize user experience in the future. At the same time, they are of great significance for optimizing the operation mode of new retail and meeting users' diverse consumption needs. Furthermore, they offer practical insights for enhancing the integration of AI technology to improve service efficiency, operational processes, and customer satisfaction, further supporting the sustainable growth and competitiveness of unmanned supermarkets in the evolving retail landscape.